Digital Competence on the Role of Office Workers: A Systematic Literature Review - Paoki, Rouna Meisda; Moedjahedy, Jimmy (SEIKO : Journal of Management & Business, 2023)
It is imperative for today's professionals to acquire the necessary competence and abilities in the fields of technology and digitalization, such as competence and skill. The level of readiness that an individual possesses in terms of their digital abilities is the degree to which they are able to efficiently accomplish tasks and meet the needs of their jobs in the digital era. The objective of this study is to conduct an extensive examination of existing literature pertaining to the current demand for digital or technology abilities, as well as to identify the specific skills or competencies that are necessary within the realm of technology. The research conducted a systematic literature review approach, following the PRISMA 2020 technique. A comprehensive review was conducted on a total of 296 publications sourced from the Scopus and Google Scholar databases from 2018-2023. Following the synthesis process, a total of 36 papers were selected for review. The collected results and findings encompass the contemporary digital competencies required in the present era, which include digital communication channels, virtual reality, remote work, digital collaboration, and digital critical thinking.